Validating dynamic crush response of unidirectional carbon fibre tube via finite element analysis method using LS-DYNA. Issue 1 (February 2021) - Samuel, R; Asadi, M; Tarda, A; Simbotin, G; Markopoulos, A P
Abstract: Crashworthiness of composite structures is of significant interest to manufacturers and operators as composites become more commonly used in automobiles and aircraft. Experimental crush testing remains an important tool in the design of subfloor fuselage structures for crashworthiness, as numerical simulations are still largely unable to accurately predict the crushing response of complex composite structures. In this paper, dynamic crush testing of carbon-fibre/epoxy specimens experimental result is validated using the modelling and simulation software LS-DYNA to understand impact behaviours under dynamic loading for finite element simulations. The tubular finite element model was modelled using MAT54 and was impacted by a 65KG rigid wall impactor with an impact velocity of 55 km/h. Material card parameters were evaluated to understand crush behaviour of the FE model. Upon analysis the experimental results and the FEA results showed a good correlation. Modelling criteria used for this model can be further used to simulate crush response of unidirectional carbon tubes under dynamic impact.